Chemically grown highly crystalline PbS thin films with ethylenediamine tetraacetic acid complexing agent. (1st November 2021) - Chalapathi, U.; Park, Si-Hyun; Choi, Won Jun
Abstract: Lead sulphide (PbS), is an excellent material for optoelectronic devices owing to its tunable optical and electrical properties. PbS is largely synthesized by chemical bath deposition (CBD) method using different complexing agents. We have grown PbS thin films by CBD method using ethylenediamine tetraacetic acid (EDTA) as the complexing agent. The effects of EDTA concentration and the bath temperature were chosen for the investigation to fabricate highly crystalline PbS films. The concentration of EDTA has been varied from 0 to 40 mM and kept the other precursors as constant in the solution. The addition of 10 mM EDTA to the solution has increased the PbS film thickness to 1 . 3 μ m . EDTA has promoted the growth of (200) oriented PbS cubic crystals with decreased hole mobilities due to the reduced grain sizes. Its direct optical band gap energy decreases from 0.42 to 0.41 eV on increasing the EDTA concentration. The PbS films deposited at different bath temperatures (40–60 °C) at an optimized EDTA concentration of 10 mM showed an enhancement in the crystallinity and modified the PbS growth direction to (111) plane. The grain size predominantly increased and the shape of the grains has turned into perfect cubic crystals aligned semi-vertical to the substrate. The electrical resistivity of the films decreased from 0.79 to 0.25 Ω cm, and the hole mobilities improved from 18.3 to 46.6 cm 2 V −1 s −1 on increasing the bath temperature from 30 to 60 °C. In contrast with other complexing agents, EDTA has shown favourable conditions for the growth of large-grained PbS thin films with improved hole mobilities, which is beneficial for its use in IR photodetectors. Graphical abstract: Highlights: PbS thin films prepared by CBD method using EDTA as the complexing agent. Effects of EDTA and bath temperature were studied to optimize PbS film growth 10 mM EDTA increases film thickness, reduces grain size, and hole mobility of PbS. Bath temperature above 40 °C enhances the grain size, and hole mobility of PbS films. Highly crystalline PbS films obtained with 10 mM EDTA and bath temperatures ≥ 40 °C.